Behavioural Portfolio Selection and Optimisation: Equities versus Cryptocurrencies. Issue 2 (2nd April 2020) - Ababio, Kofi Agyarko
ABSTRACT: This paper investigates if real investors other than rational investors could add value to their investment portfolios considering their mentality and psychology. The universe of assets constitutes 21 cryptocurrencies (37 international equities) and covers, respectively, the period from August 1, 2016, to March 31, 2018 (January 7, 2002, to March 23, 2018). The cumulative prospect theory and variant specifications were utilized to validate and compare the classification and selection of assets driven by some decision theories. The results of optimization analysis of all the formulated portfolios constituting assets from both markets showed that portfolios constituting assets with lower cumulative prospect theory values outperformed their counterpart with higher cumulative prospect theory values. The superiority of the cumulative prospect theory was established as an empirically corroborated theory of decision-making with rich psychological content. The findings of this paper are crucial for finance practitioners as they showcase an intuitive and coherent manner to guide fund managers, investors and other economic agents in their investment practices.